Hydrogen Materials Science and Chemistry of Carbon Nanomaterials [electronic resource] - NATO Advanced Research Workshop on Hydrogen Materials Science and Chemistry of Carbon Nanomaterial (8th : 2003 : Sudak, Ukraine); Veziroglu, T. Nejat.; SpringerLink (Online service) (Dordrecht : Springer Science+Business Media B.V., 2007)
PSZJBL